Environmental determinants of recruitment and their influence on the population dynamics of stream-living brown trout Salmo trutta - Lobon-Cervia, J; Rincon, P A (Oikos, 2004)
The relative importance of endogenous feedback mechanism vs environmental factors in the dynamics of animal populations is a long-standing, but not fully resolved yet, issue in ecology. We have addressed this subject by examining the dynamics of a stream-resident population of Salmo trutta in a northwestern Spain stream. Recruitment was the major determinant of population size and the abundance of recruits resulted from a combination of regional and local environmental factors. Stream discharge in March determined the amount of stream area suitable for newly emerged trout ( r2=0.59-0.79%), that in turn determined the abundance of recruits at each site ( r2=0.51-0.77%). Stream discharge determines the overall strength of annual recruitment. Discharge, however, combines with stream morphology at the site scale to result in a site-specific area suitable for juveniles and, hence, site-specific recruitment. Thus, our study exemplifies how an environmentally driven animal population may persist on time with little or no operation of endogenous regulatory mechanisms.